Emigrer en contexte colonial : La vague de départ des fellahs du Constantinois en 1910 - Salma Hargal (Revue des Mondes Musulmans et de la Méditerranée)
In March 1910, hundreds of Algerian peasants landed in the port of Beirut. Meanwhile in Algeria, many peasants were still applying for foreign-travel passports at the office center of Constantine and others were emigrating without any official document. French authorities were profoundly worried about these population movements. Therefore, the French government in Algeria charged local administrators to investigate the circumstances of these migrations at the level of their territorial units. This study draws on various reports and petitions produced in this context in order to understand the process of Algerian peasant migration into the Ottoman Empire. It further reveals the remarkable agency of migrants who also used the legal procedure of obtaining passports to Great Syria as a way to get their complaints heard by the French government of Algeria.